Kekerasan Seksual Pada Anak Dan Perempuan Dalam Prespektif Penology - Ilusya Nurussaadah (Hakim, 2023)
Violence against children is anything that make children tormented, both physically, psychologically and mentally. Violence against children is an act of persecution or mistreatment of children in the form of physical, emotional, sexual abuse, neglect of parenting and exploitation for profit commercially real or innocuous harm health, survival, dignity or development, acts of violence obtained from the person responsible, trusted or authorized in the protection of the child.